2004
DOI: 10.1111/j.1365-2133.2004.05707.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus-lichen planus overlap in a patient with hepatitis C virus infection

Abstract: Influence of environmental temperature on the occurrence of non-necrotizing cellulitis of the leg SIR, Non-necrotizing cellulitis of the leg is a common cutaneous bacterial infection whose risk factors include venous insufficiency, lymphoedema and toe-web intertrigo. The role of environmental temperature remains controversial. 1 To study the relationship between environmental temperature and the frequency of non-necrotizing cellulitis of the leg, we reviewed all patients hospitalized with nonnecrotizing cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Regarding overlapping syndrome VLP/VLS, some authors (8,32,33) have suggested that these two aspects may represent a transitional stage to a unique disease rather than the coexistence of two distinct entities (8). In our opinion, differential diagnosis between VLP and VLS is difficult, particularly in the late stage of disease when fibrosis aspects, typical of VLS.…”
Section: Discussionmentioning
confidence: 81%
“…Regarding overlapping syndrome VLP/VLS, some authors (8,32,33) have suggested that these two aspects may represent a transitional stage to a unique disease rather than the coexistence of two distinct entities (8). In our opinion, differential diagnosis between VLP and VLS is difficult, particularly in the late stage of disease when fibrosis aspects, typical of VLS.…”
Section: Discussionmentioning
confidence: 81%
“…6a,b). However, presence of lichenoid infiltrates in early genital LS has been acknowledged by many investigators, 4,5,23–28 and it is possible that lichenoid interface dermatitis is a fore runner in the pathogenesis of LS, which may later evolve into vacuolar interface dermatitis. Linear studies with repeated histologic examinations are needed to prove this point.…”
Section: Discussionmentioning
confidence: 99%
“…Borrelia burgdorferi or a human papilloma virus, has been postulated but there are no clear data showing that LS is related to an infection (Lau ; Nasca 2006; Nieuwenhof HP van ; Gambichler ; Edmonds ; Alonso‐Llamazares ). There are sporadic reports of LS associated with a hepatitis C infection (Shim ; Yashar ; Boulinguez ).…”
Section: Infectiousmentioning
confidence: 99%